Emerging technologies adoption in the malaysian construction industry: A systematic review - Fakhira, Khudzari; Afiqah R., Radzi; Rahimi, A. Rahman (Construction Research Institute of Malaysia, 2024)
Adopting Emerging Technologies (ET) can transform the Malaysian construction industry through improved productivity, efficiency, and sustainability. Although there is a growing body of literature on ET adoption, there remains a noticeable lack of comprehensive reviews specifically addressing the Malaysian construction industry. This study seeks to fill this gap by providing a systematic literature review (SLR) analysis of current research on ET adoption in the Malaysian construction industry. By examining 50 carefully selected and relevant journal articles, this investigation aims to highlight existing research gaps and potential future directions for industry professionals and academic researchers. The analysis revealed that prior research had studied nine groups of ETs: Advanced Materials, Artificial Intelligence (AI), Building Information Modelling (BIM), Blockchain, Cloud, Prefabrication & Modular, Internet of Things (IoT), Integrated, and Others. Also, the findings show no or limited research on five ETs that are part of the national strategic plan: 3D Printing & Additive Manufacturing, Autonomous Construction, 3D Scanning & Photogrammetry, and Big Data & Predictive Analytic. This study adds value to the existing literature by offering a comprehensive overview of research on ET adoption within the Malaysian construction industry. Moreover, identifying the knowledge gaps can illuminate potential avenues for future research in this domain. The study findings benefit industry practitioners, policymakers, and researchers interested in ET adoption in the Malaysian construction industry.